Audit fee premium: The potential effect of King III. Issue 2 (4th May 2017) - Pendehama, Vincent; Padia, Nirupa; Callaghan, Chris
Abstract : In the wake of corporate scandals at world-renowned companies such as Enron (in 2001) and WorldCom (in 2002), public confidence in the role of the auditing profession was eroded. Consequently, in the United States, the Sarbanes-Oxley Act of 2002 (SOX) introduced a raft of mandatory corporate governance initiatives; in the United Kingdom measures included expanding the role of the Financial Reporting Council, the updating of the Combined Code in 2003 and the 2005 Company Law Reform Act; while in France, the Financial Security introduced provisions which were deemed to be very similar to SOX. In South Africa, corporate reforms included the introduction of the King I to III codes of corporate governance, the Companies Act No.71 of 2008 and the Auditing Profession Act No. 26 of 2005. In particular, King III introduced the concept of integrated reporting (IR) which recommends that companies report holistically on both financial and sustainability (economic, social and environmental) issues. In contrast to SOX, however, the application of King III is voluntary, operating on an 'apply or explain' basis. The introduction of SOX was postulated to have increased compliance costs and created fee opportunities for the audit profession, giving rise to questions as to whether or not the introduction of IR in King III had introduced similar opportunities for the auditing profession in South Africa, resulting in audit firms charging an audit fee premium 1 . In this study, multiple regression analysis was conducted on two sets of models to test two hypotheses: (i) that the BIG4 2 audit firms potentially charged an audit fee premium in response to the recommendations of King III on IR, and (ii) that audit fees are related to non-audit service fees. Results of the research do not show any evidence to suggest that the advent of King III was related to audit fee premiums, yet a strong relationship was found between audit 3 and non-audit service fees 4 . Further, certain of the BIG4 audit firms were found to obtain an audit fee premium. The findings of this study add a South African dimension to the existing body of knowledge on the relationships between audit fees and governance initiatives in this context.